Corylus avellana 'Contorta' Contorted European Filbert, Henry Lauder's Walking Stick - Edward Gilman (EDIS, 2007)
This document provides an overview of the Contorted European Filbert (Corylus avellana ‘Contorta’), also known as Henry Lauder’s Walking Stick. It describes the plant’s unique twisted stems and branches, its growth habits, and its ornamental features. The shrub is noted for its winter interest, drought tolerance, and suitability for various landscape uses. The document also includes details on its planting requirements, hardiness zones, and potential uses in garden design. Additionally, it mentions the plant’s resistance to pests and a reported foliage and twig blight. Original publication date October 1999.